2021
DOI: 10.15562/ism.v12i1.951
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic improvement in severe-critical COVID-19 patient after tocilizumab administration: a clinical experience

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in coronavirus disease 2019 (COVID-19) involve so many inflammatory cytokines, especially Interleukin-6 (IL-6). The usage of tocilizumab as an anti-IL-6 receptor antibody had been approved as COVID-19 medication.Case Presentation: This article reports a 51-year-old woman diagnosed with severe-critical COVID-19. The patient made significant progress after tocilizumab administration. The patient was hospitalized for 14 days befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this study, the cough already decreased a half after day 7 and was only found at 16.7% on day 14, this is consistent with the manifestation was gotten better along with negative virus. [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the cough already decreased a half after day 7 and was only found at 16.7% on day 14, this is consistent with the manifestation was gotten better along with negative virus. [16].…”
Section: Discussionmentioning
confidence: 99%